Who Pays for Maritime Security? Burden Sharing and International Legal Constraints in the Strait of Malacca and Indonesian Archipelagic Sea Lanes - Hartanto, Dhimas Rudy; Renmaur, Aldi Giovano (Journal Politique, 2026)
The Strait of Malacca and Indonesia's Archipelagic Sea Lanes (ALKI) facilitating  approximately  25  percent  of  global  seaborne  trade  and roughly 80 percent of East Asia's crude oil supply annually. This article develops  the  concept  of asymmetrical  maritime  governance  burden to explain  how  UNCLOS  structurally  privileges  navigational  freedom while  consigning  disproportionate  security  responsibilities  to  littoral developing states, notably Indonesia. Through qualitative method with juridical analysis, empirical examination of maritime incident data, and a  comparative  study  of  international  chokepoints.  The  article demonstrates  that  existing  cooperative  mechanisms  under  Article  43 remain institutionally weak, politically fragile, and fiscally inadequate. The article argues that unless UNCLOS's lacuna on burden financing is addressed  through  a  negotiated  protocol  or  binding  regional agreement,  the  structural  inequality  between  littoral  states  and  user states will deepen, threatening long-term navigational security in one of the world's most strategically indispensable waterways.